Velocity fluctuations and population distribution in clusters of settling particles at low Reynolds number - Boschan, Alejandro (2016)
A study on the spatial organization and velocity fluctuations of non-Brownian spherical particles settling at low Reynolds number in a vertical Hele-Shaw cell is reported. The particle volume fraction ranged from 0.005 to 0.05, while the distance between cell plates ranged from 5 to 15 times the particle radius. Particle tracking revealed that particles were not uniformly distributed in space but assembled in transient settling clusters. The population distribution of these clusters followed an exponential law. The measured velocity fluctuations are in agreement with that predicted theoretically for spherical clusters, from the balance between the apparent weight and the drag force. This result suggests that particle clustering, more than a spatial distribution of particles derived from random and independent events, is at the origin of the velocity fluctuations.